On Materiality: Home Spaces and Objects as Expanding Elements of Everyday Experiences - Arcidiacono, Francesco; Pontecorvo, Clotilde (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
In this article, using a multidimensional methodology, we explored the role of materiality in the everyday lives of eight Italian families. Focusing on spaces and objects, we analyzed how people "use" material frames and boundaries in expanding their individual and collective experiences at home. We employed a composite design including different sources of data: audio and videotaped home tours, visual ethnographic notes and photos, observations of everyday family activities, home-mapping and observational tracking of actions at regular intervals. We used discourse and conversation analysis to investigate family members' talk-in-interaction concerning materiality. The findings show that spaces and objects are expansions of participants' everyday activities: they are presented as flexible in their use, multifunctional and affectively connoted. We also present implications for the methodological design and its potential for capturing how family doings create both a sense of life and the affordances of everyday experiences at home.